Novel light trapping techniques for silicon solar cells. - Khalifa, Ahmed Emad (AUC Knowledge Fountain, 2016)
Thin-film silicon photovoltaic (PV) solar cells have attracted significant interest for decades due to the increasing demand for clean and sustainable energy resources. Further reduction of the cost of materials and manufacturing processes is required to reach the grid parity where the cost of electricity from solar PV cells is equal to the cost of other nonrenewable resources. Crystalline and thin-film silicon solar cells are anticipated to continue to be one of the dominant solar PV cell technologies. This anticipation is due to the abundance of silicon and the successful history of a continuous drop in cost in silicon-based PV cells. In this thesis, several designs were investigated to enhance absorption of sunlight in the active layers of silicon-based solar cells. In the first design, a plasmonic enhancement to silicon solar cells using (Titanium nitride) TiN as a replacement for silver is studied. In the second, a new design for tandem thin-film silicon solar cells is proposed using a periodic layer between the two subcells. Finally, a low-cost easily fabricated nanocone facial textures is proposed and showed promising experimental and simulation antireflection properties. 3D electromagnetic analysis was performed using finite difference time domain (FDTD) simulations to all structures and 3D Device simulations were additionally used to study the tandem cell structure. These contributions which were published are believed to contribute towards achieving high efficiency and cost-effective solar cells.